First Improving the quality of education through the use of individual assignments in classroom mathematics lessons - Saidova Mohinur Jonpoʻlatovna; Fayziyeva Marjona Amonjonovna (Genius Journals, 2022)
This article discusses the concept of individuality, the types and tasks of individual assignments, and the importance of individual assignments in first grade math classes.
Keywords: Individuality; individual assignment; first grade math lessons; assignment